A questão de gênero na Base Nacional Comum Curricular: percepções dos professores de História dos anos finais do Ensino Fundamental de uma cidade da Região do Alto Uruguai/RS - Vicrovski, Alessandra Kátia (2020)
The present work has as its theme of study the National Common Curriculum Base and Gender Studies. The present work aims to identify in the BNCC, with regard to the final years of elementary school, whether there are (or not) discussions about Gender, so that in this way we can understand what are the perceptions of history teachers about this concept for the discipline. Thus, the investigation originates in the problem: The National Common Curriculum Base (BNCC), which refers to the stage of elementary school approved in 2017, propose (or not) to work with the concept of Gender? Based on your guidelines, what are the perceptions of history teachers from the 6th to the 9th grade of elementary school, from four state schools in the municipality of Erechim of the State of Rio Grande do Sul, about this concept for the discipline? The research proposal is qualitative in nature, and was guided by the descriptive-interpretative approach, through bibliographic research, Documentary and field research, having as universe researched four State schools of the municipality Erechim/ RS, which include the 15th Regional Coordination of Education. The subjects involved in this research, through semi-structured interviews, were five elementary school teachers who taught the discipline of history between the 6th and 9th grade. For the analysis of data emerged from semi-structured interviews with teachers and the BNCC Documentary Study, it was based on Bardin's content analysis proposal (1977). At the end of this research, it was possible to conclude that the interviewed teachers do not ignore the importance of discussing gender in history classes, however, it was evident that the perceptions of these subjects about what gender is, require a lack of in-depth theoretical knowledge on the theme. This has led teachers to relate gender again and again as if it were synonymous with sexual choice. On the other hand, bncc could not identify discussions about gender in its analyzed chapters. However, there was an attempt by BNNC to present the following themes: diversity; difference; Prejudice. However, the document does not explain what are the theoretical and conceptual foundations for these terms, which makes it difficult to reflect on the way in which this document appropriates these concepts.